Planned Birth Campaigns in China, 1949-1976. Case Study No. 5 - Chu, Leonard L.; Hawaii Univ., Honolulu. East-West Center (Washington, D.C. : Distributed by ERIC Clearinghouse, 1977)
National planned birth policy decisions in the People's Republic of China from 1949 to 1976 and the organizational infrastructure that supports such decisions are reviewed in this monograph. The transferability and limitations of the Chinese experience are also discussed. Specific topics covered are: the development of the planned birth campaigns; organization, information, education, and communication in the campaigns; and the contents and effects of planned birth propaganda. Appendixes contain discussions of population in China and a translation of a Chinese newspaper article urging men to live with their wives' families after marriage. (Author/FL)
Includes bibliographical references.
Microfiche.
Keywords: Asian History; Communication Research; Communication (Thought Transfer); Communism; Family Planning; Foreign Countries; Information Theory; Mass Media; Policy Formation; Population Education; Population Trends; Propaganda; China; Reports, Research